Supervision of Self-Declared Halal Certification Under Government Regulation No. 39/2021: A Sadd Al-Dzarī’ah Perspective - Mila Dwi Apriyani; Andi Cahyono (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2025)
This study explores the supervision of the self-declared halal certification system under Government Regulation No. 39 of 2021 on the Administration of Halal Product Assurance, analyzed through the sadd al-dzarī'ah perspective. The research focuses on the mechanism for supervising self-declared certifications, identifying potential deviations, and proposing solutions through sadd al-dzarī'ah, which emphasizes preventing risks that could harm society. Using a qualitative normative legal method, this study incorporates a statutory approach and literature review, supported by secondary data from legal documents and interviews with relevant institutions and business actors. The findings highlight challenges in supervising self-declarations, such as limited human resources, inadequate infrastructure, and difficulties in ensuring compliance among businesses. While self-declaration aims to simplify the certification process for micro and small enterprises, insufficient monitoring jeopardizes public trust in product halal integrity. From the sadd al-dzarī'ah perspective, strengthening this regulation is necessary to mitigate violations by expanding the number of supervisors, leveraging monitoring technologies, and raising awareness about halal compliance. These efforts can enhance the effectiveness of the self-declaration system, improve consumer confidence, and bolster Indonesia's reputation in the global halal industry. The study calls for comprehensive policy revisions to ensure the program's accountability and sustainability.